Label‐Free Quantitative Proteomics of Enriched Nuclei from Sugarcane (Saccharum ssp) Stems in Response to Drought Stress. Issue 14 (4th July 2019) - Salvato, Fernanda; Loziuk, Philip; Kiyota, Eduardo; Daneluzzi, Gabriel Silva; Araújo, Pedro; Muddiman, David C.; Mazzafera, Paulo
Abstract: Drought is considered the major abiotic stress limiting crop productivity. This study seeks to identify proteins involved in the drought response in sugarcane stems submitted to drought stress. The integration of nuclei enrichment sample preparation with the shotgun proteomic approach results in great coverage of the sugarcane stem proteome with 5381 protein groups identified. A total of 1204 differentially accumulated proteins are detected in response to drought, among which 586 and 618 are increased and reduced in abundance, respectively. A total of 115 exclusive proteins are detected, being 41 exclusives of drought‐stressed plants and 74 exclusives of control plants. In the control plants, most of these proteins are related to cell wall metabolism, indicating that drought affects negatively the cell wall metabolism. Also, 37 transcription factors (TFs) are identified, which are low abundant nuclear proteins and are differentially accumulated in response to drought stress. These TFs are associated to protein domains such as leucine‐rich (bZIP), C2H2, NAC, C3H, LIM, Myb‐related, heat shock factor (HSF) and auxin response factor (ARF). Increased abundance of chromatin remodeling and RNA processing proteins are also observed. It is suggested that these variations result from an imbalance of protein synthesis and degradation processes induced by drought.